Carbon-Binder Weight Loading Optimization for Improved Lithium-Ion Battery Rate Capability. Issue 7 (1st July 2022) - Usseglio-Viretta, Francois L. E.; Colclasure, Andrew M.; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew N.; Abraham, Daniel P.; Rodrigues, Marco-Tulio F.; Dufek, Eric J.; Tanim, Tanvir R.; Chinnam, Parameswara R.; Ha, Yeyoung; Smith, Kandler
Abstract : Battery performance is strongly correlated with electrode microstructure and weight loading of the electrode components. Among them are the carbon-black and binder additives that enhance effective conductivity and provide mechanical integrity. However, these both reduce effective ionic transport in the electrolyte phase and reduce energy density. Therefore, an optimal additive loading is required to maximize performance, especially for fast charging where ionic transport is essential. Such optimization analysis is however challenging due to the nanoscale imaging limitations that prevent characterizing this additive phase and thus quantifying its impact on performance. Herein, an additive-phase generation algorithm has been developed to remedy this limitation and identify percolation threshold used to define a minimal additive loading. Improved ionic transport coefficients from reducing additive loading has been then quantified through homogenization calculation, macroscale model fitting, and experimental symmetric cell measurement, with good agreement between the methods. Rate capability test demonstrates capacity improvement at fast charge at the beginning of life, from 37% to 55%, respectively for high and low additive loading during 6C CC charging, in agreement with macroscale model, and attributed to a combination of lower cathode impedance, reduced electrode tortuosity and cathode thickness.